Covergence of Industry Labor Productivity among Advanced Economies, 1963-1982 - Dollar, David; Wolff, Edward N. (The Review of Economics and Statistics, 1988)
Data are used for thirteen industrialized countries to investigate convergence of labor productivity levels in individual manufacturing industries over the 1963-82 period. The authors find convergence in virtually every manufacturing industry. Among these countries, the co efficient of variation of industry labor productivity declined in all but one of twenty-eight industries. However, productivity convergenc e is stronger for all manufacturing than within individual industries, especially heavy and high-technology industries. Also, variation in employment mix among countries plays little role in explaining cross-country differences i n aggregate manufacturing productivity, nor have changes in employment mixes been an important source of convergence. Copyright 1988 by MIT Press.